Technical Deep Dive: MuleSoft’s API-Led Architecture in Modern Banking Payment Systems - Venugopal Reddy Depa (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This technical article examines the architectural framework and implementation methodology of MuleSoft’s Anypoint Platform in modern banking payment systems. The article analyzes the platform’s API-led connectivity approach, exploring its three-layer architecture comprising experience APIs, Process APIs, and system APIs. The article covers system integration patterns, security implementations, performance optimization strategies, and disaster recovery mechanisms. The article demonstrates how MuleSoft’s architecture enables financial institutions to achieve robust payment processing capabilities while maintaining high availability, security, and scalability. Furthermore, it explores emerging technologies, including blockchain integration, AI-driven analytics, and edge computing implementations that shape the future of payment systems.